Controlled release kinetics from a surface modified microgel-based reservoir device. Issue 12 (20th February 2015) - Guo, Siyuan; Gao, Yongfeng; Wei, Menglian; Zhang, Qiang Matthew; Serpe, Michael J.
Abstract : Deposition of Si-based layers on top of a polymer-based "drug" delivery device allows fine-tuning of "drug" release kinetics. Abstract : A device constructed by sandwiching a thin film of poly( N -isopropylacrylamide)- co -acrylic acid (pNIPAm- co -AAc) microgels between two thin layers of Au (all on a glass support) was used as a novel platform for controlled release of small molecules (drugs). In this submission, the model drug tris (4-(dimenthylamino)phenyl)methylium chloride (Crystal Violet, CV) was loaded into the microgel layer of the device by electrostatic interaction of its positive charge with the negative charges on the deprotonated AAc groups on the microgels at pH > 6.5. The upper Au layer of this device was coated with SiO2 generated by hydrolysis of tetraethyl orthosilicate (TEOS) catalyzed by ammonia at room temperature. Upon exposing the CV loaded devices to pH 3 solutions, the microgel AAc groups were neutralized, and the CV released. The release rate of the CV could be controlled by the thickness of the SiO2 layer coating the Au layer. Specifically, devices with thick silica layers slow the release rate and thin layers allow for faster release. This device represents an easily fabricated device for controlled and triggered release from a thin film with easily controlled release kinetics.